Emotional climate in infancy: psychometric properties and predictors of the infant five-minute speech sample - Reinelt, Tilman; Şamdan, Gizem; Rothenfußer, Selina; Alvater, Jana Tabea; Pauen, Sabina (Journal of child and family studies, 2025)
The Five Minute Speech Sample (FMSS) is an economical and reliable method for assessing emotional climate. This study aims to create a German infant version of the FMSS (IFMSS) and examine relations to demographic characteristics; investigate the association between IFMSS “critical comments” and maternal depressive symptoms; explore whether IFMSS categories are more affected by infant-related strains than maternal depressive symptoms; and determine to which extent social support can modulate the association of depressive symptoms and infant-related strains with emotional climate in the dyad. A total of 90 socially and/or culturally disadvantaged mothers from Germany, participating in “The Bremen Initiative to Foster Early Childhood Development”, were asked to talk for five minutes about their infants at three months postpartum. These speech samples were coded using the IFMSS manual. Maternal depressive symptoms, infant-related strains, and perceived social support were measured via questionnaires at the same time point. The IFMSS codings showed adequate inter-rater reliability, and were unrelated to demographic variables, suggesting that the German IFMSS is objective and test-fair. Consistent with previous research, mothers with higher levels of depressive symptoms were more likely to make critical comments about their infants, although the frequency of these comments depended more on infant-related strains than on depressive symptoms. Finally, social support moderated the negative effects of infant-related strains and depressive symptoms on emotional climate. The German IFMSS can be reliably used in early infancy. Infant-related strains might particularly affect the emotional climate between mother and child.
Online veröffentlicht: 27. September 2025, Artikelversion: 13. November 2025
Gesehen am 17.02.2026